Fundamentals of performance improvement optimizing results through people, process, and organizations : interventions, performance support tools, case studes - Van Tiem, Darlene M.; Moseley, James L. (James Lee), 1942-; Dessinger, Joan Conway; Van Tiem, Darlene M.; Van Tiem, Darlene M.; ProQuest (Firm) (San Francisco, Calif. : Pfeiffer, 2012)
"Fundamentals of Performance Improvement is a practical how-to guide designed to help practitioners and students understand the science of performance technology and successfully implement organizational change. Using the Human Performance Technology (HTP) model, the authors explain step-by-step how to spot performance indicators, analyze problems, identify their underlying causes, and create workable solutions, and perspective on change management. The completely updated and revised third edition will also feature expanded sections on intervention design and development, tips for sustaining change over time, and all new case studies contributed by top practitioners and academics in the field"--
"The third edition of Fundamentals of Performance Improvement began as a project to revise Fundamentals of Performance Technology and Performance Improvement Interventions and combine them into one book. However, performance improvement is advancing rapidly and our task ... became updating the contents of both books"--Acknowledgments.
Includes bibliographical references and indexes.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Performance technology; Performance; Personnel management; Electronic books